A Statistical Assessment of the Competitiveness of the Industrial Sector in the Kharkiv Region - Sozanskyy, L. Yo. (Statistics of Ukraine, 2021)
Industry is the leading sector in the economy of Kharkiv region. Its share in the economic structure of the region was 33.1% in 2018 (against 21.3% in 2012). The purpose of the article is to provide statistical and analytical justification of the competitiveness of the industrial sector in the Kharkiv region. This goal was achieved by a comparative assessment of the industry performance in the Kharkiv region and Ukraine in general by the following set of criteria: product innovation, operating surplus and average monthly salary. Using these criteria, the product innovation and socio-economic efficiency of the industry operation and industry companies was assessed. The assessment revealed that the manufacturing industry had the strongest advantages among the industrial activities in the Kharkiv region. Machinery and equipment not classified in other groups has the dominant position in the manufacturing by a number of advantages (10 out of 14). Also, a relatively large number of advantages were found in other machine-building industries of the region. Food, woodworking, furniture and pharmaceuticals is another group of industries in the Kharkiv region with a high competitive capacity. The vast majority of other manufacturing industries in the region have some advantages in product innovation segments (rubber and plastic products, other non-metallic mineral products; chemicals and chemical products; textiles, clothing, leather, leather products and other materials) or socio-economic efficiency (metallurgy, finished metal products, except for machinery and equipment). It is demonstrated that high shares (for some positions – monopoly shares) of the Kharkiv regions in the total industrial output of Ukraine are indications of technical and technological, resource, organizational and economic advantages and/or higher efficiency and innovativeness of products made by some regional industries. It is stressed that further development and stimulation of these industries are capable of laying the background required for the enhancement of competitive advantages.